2005
DOI: 10.1063/1.1879972
|View full text |Cite
|
Sign up to set email alerts
|

Bound-state energies in argon trimers via a variational expansion: The effects from many-body corrections

Abstract: In this paper we study the bound-state energies and geometries of Ar 3 for J = 0, using the distributed Gaussian functions method that provides a configurational description of the different structures contributing to these states. Atom-atom potentials are employed and three-body long-range effects are also included in the computational treatment by adding to the sum of potentials the AxilrodTeller triple-dipole correction for the whole rotationless energy spectrum. An estimate of the total number of bound sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…While these contributions are very small in neutral He clusters [28], they may be of some importance when an ionic impurity is present. In the latter case, in fact, the main contribution to the many body interaction terms comes from the fact that the He atoms near the impurity are polarized by the charge and acquire a small dipole moment.…”
Section: The Potentialsmentioning
confidence: 99%
“…While these contributions are very small in neutral He clusters [28], they may be of some importance when an ionic impurity is present. In the latter case, in fact, the main contribution to the many body interaction terms comes from the fact that the He atoms near the impurity are polarized by the charge and acquire a small dipole moment.…”
Section: The Potentialsmentioning
confidence: 99%
“…[24] and which we know to provide at long range the Axilrod-Teller (AT) contribution to the full interaction [25]. In our previous study on the Ar 3 system, however, we had found [12] that the AT corrections were not very significant and did not substantially modify its spectral structure. Since we are dealing here with much more weakly interacting partners (in the HeNeH three-atom complex, at least) we did not consider it necessary to test its effects on the single bound state of the neutral cluster [14].…”
Section: B the 3b Correctionsmentioning
confidence: 89%
“…The latter method has been presented many times before [9][10][11][12][13] and therefore only a short summary of its implementation will be given below, referring any interested reader to our earlier publications. Section III describes the 2B potentials employed for the two title systems and the 3B corrections which we have included, while Section IV presents our results.…”
Section: Searching For Many-body Effects and Efimov States Inmentioning
confidence: 99%
“…They do so via London dispersion or more general van der Waals (vdW) interactions. [6][7][8][9][10][11] The resultant "vdW clusters" are thus only weakly bound, and manifest bound states with high probability at extremely large nuclear separations-in comparison, e.g., with covalently bonded species. As a consequence, vdW clusters are inherently "floppy," meaning that they have very strong coupling between their rotational and vibrational degrees of freedom, and also exhibit highly delocalized or "fluxional" bound state wavefunctions.…”
Section: Introductionmentioning
confidence: 98%